Multiobjective Optimisation of Restricted Complexity Controllers - Cao, Yi; Yan, Wenjun (Lavoisier, 2003)
Restricted complexity controller design for the active suspension benchmark problem call for papers EJC special issue on Design and Optimisation of Restricted Complexity Controllers. Web site http:/www-ejc.ensieg. inpg.fr/, 2002 is considered. T he control design specifications of the benchmark is firstly recast intoamixed HI/l1 optimisation problem, which is solved viaaconvex optimisation approach. A globally optimal Pareto curve is produced via the optimisation. It presents the limits of performance and is served asareference for restricted complexity controller design. Then, controllers with different complexity are designed viaadirect optimisation approach. The performance indices of these controllers are compared with the global Pareto curve. Based on the comparison, the controller with three parameters is determined as the one achieving acceptable performance with lowest complexity. Experimental results on the real system confirm the satisfactory performance achieved by the controller.